Angiogenesis in Non-Hodgkin's Lymphoma: An Intercategory Comparison of Microvessel Density. (27th March 2012) - Aggarwal, Deepti; Srivastava, Gunjan; Gupta, Ruchika; Pant, Leela; Krishan, Gopal; Singh, Sompal
Abstract : Background . This study was aimed at comparing angiogenesis, seen as microvessel density (MVD) in subtypes of non-Hodgkin's lymphoma (NHL). Methods . In this study, 64 cases of NHL diagnosed over a three-year period were included along with 15 lymph node biopsies of reactive hyperplasia. NHLs were classified using REAL classification, and immunohistochemistry was performed for CD34 in all cases. CD34-stained sections were evaluated for "hot spots, " where MVD was assessed and expressed as per mm 2 . Appropriate statistical methods were applied. Results . There were 6 cases of well-differentiated lymphocytic lymphoma (SLL), 21 diffuse large B-cell lymphoma (DLBCL), 15 follicular lymphoma, 10 lymphoblastic lymphoma, 7 MALToma, and 5 peripheral T-cell lymphoma (PTCL). Mean MVD was highest in reactive hyperplasia (191.92 ± 12.16 per mm 2 ) compared to all NHLs. Among NHLs, PTCL demonstrated the highest MVD (183.42 ± 8.24 ) followed by DLBCL (149 .91 ± 13 .68 ). A significant difference was found in MVD between reactive and individual lymphoma groups. SLL had significantly lower MVD than other lymphoma subtypes. Conclusion . Angiogenesis, assessed by MVD, showed significant differences among subtypes of NHL, especially the indolent types like SLL. The higher MVD in aggressive lymphomas like PTCL and DLBCL can potentially be utilized in targeted therapy with antiangiogenic drugs.